PERBEDAAN KADAR FERITIN PADA IBU HAMIL DENGAN COVID-19 TANPA DAN DISERTAI PREEKLAMPSIA Penelitian di RSUD Ulin Banjarmasin Periode Maret 2020- Periode Maret 2020-Februari 2022 - Rahmatullah, Muhammad Ikhsan; Armanza, Ferry; Hendriyono, Fransiskus Xaverius; Aditya, Renny; Rahmiati, Rahmiati (Universitas Lambung Mangkurat, 2023)
COVID-19 is an infectious disease which become a pandemic worldwide. Pregnant women are a vulnerable group infected with COVID-19. Ferritin is a marker of increased inflammation associated with the severity of COVID-19. Pregnant women with COVID-19 have a higher mortality than pregnant women without COVID-19. Low ferritin levels during 28-30 weeks of gestation are associated with a low incidence of preeclampsia. This study aims to determine whether there are significant feritin level difference in pregnant women with COVID-19 without and with preeclampsia. This type of research is analytic observational using a cross-sectional study design with retrospective data collection. The results of the study obtained 603 subjects, but only 63 subjects met the inclusion criteria. Pregnant women with COVID-19 without preeclampsia as 36 subjects were randomized thus obtained 27 subjects were pregnant women with COVID-19 without preeclampsia and 27 subjects were pregnant women with COVID-19 accompanied by preeclampsia. Pregnant women with COVID-19 without preeclampsia had a median 66 ng/mL with a minimum value 1 ng/mL and a maximum value 951 ng/mL and pregnant women with COVID-19 accompanied by preeclampsia had a median 55 ng/mL with a minimum value 2 ng/mL and a maximum value 1.112 ng/mL. The conclusion of this study was that there was no significant feritin level difference in pregnant women with COVID-19 without and with preeclampsia with p=0.924.